Learning management according to Yonisomanasikara principles to enhance learners’ desirable characteristics - yodboon, pornpirom (Journal of MCU Buddhasothorn Review, 2022)
Learning management is an important process in bringing the curriculum into practice in the classroom so that learners meet the quality required by the curriculum. And for the most effective learning management in the development of learners The author therefore presents the principle of Yonisomanasikara, which is a valuable concept in Buddhism, to be applied to learning management to enhance the desirable characteristics of the learners. By giving students the opportunity to know things according to the learning process that he is good at. together with classroom activities. Therefore, teachers must have knowledge and understanding of the principles, concepts and focus related to learning management according to the Yonisomanasikara principle in order to enhance students’ desirable characteristics. so that it can be applied to various learning activities both inside and outside the school able to enhance the students’ 8 desirable characteristics, namely patriotism, religion, monarchy, honesty Discipline to learn live in sufficiency committed to work Love being Thai and having a public mind. It also affects the development of the mind and thinking properly and also affects the quality of life in a good way.